2004
DOI: 10.1073/pnas.0406771101
|View full text |Cite|
|
Sign up to set email alerts
|

Transforming growth factor β-induced cell cycle arrest of human hematopoietic cells requires p57KIP2 up-regulation

Abstract: Transforming growth factor β (TGFβ) is one of few known negative regulators of hematopoiesis, yet the mechanisms by which it affects cell cycle arrest and stem cell quiescence are poorly understood. Induction of the cyclin-dependent kinase inhibitors, p15INK4b (p15) and p21WAF1 (p21) is important for TGFβ-mediated cytostasis in epithelial cells but not in hematopoietic cells. Using primary human hematopoietic cells and microarray analysis, we identified p57KIP2 (p57) as the only cyclin-dependent kinase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
196
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(212 citation statements)
references
References 44 publications
14
196
0
2
Order By: Relevance
“…To investigate how TGFβ affects p57 regulation in primary HSPCs over time, we performed a time course qPCR experiment where freshly sorted murine LSKCD34 -cells (HSCs) or LSKCD34 + cells (hematopoietic progenitor cells) were treated with TGFβ and harvested at different time points (Fig 1A). In agreement with earlier studies 13,14 , qPCR analysis of p57 expression revealed a strong upregulation at 5 h (2.8-fold, P=0.045) and 12 h (6.4-fold; P=0.018) following TGFβ treatment, in the hematopoietic progenitor population ( Fig 1B). However, when protein translation was blocked by cycloheximide treatment, TGFβ-induced upregulation of p57 was effectively diminished (<1.3-fold; Fig 1C).…”
Section: P57 Expression Is Indirectly Upregulated By Tgfβ In Primitivsupporting
confidence: 92%
See 4 more Smart Citations
“…To investigate how TGFβ affects p57 regulation in primary HSPCs over time, we performed a time course qPCR experiment where freshly sorted murine LSKCD34 -cells (HSCs) or LSKCD34 + cells (hematopoietic progenitor cells) were treated with TGFβ and harvested at different time points (Fig 1A). In agreement with earlier studies 13,14 , qPCR analysis of p57 expression revealed a strong upregulation at 5 h (2.8-fold, P=0.045) and 12 h (6.4-fold; P=0.018) following TGFβ treatment, in the hematopoietic progenitor population ( Fig 1B). However, when protein translation was blocked by cycloheximide treatment, TGFβ-induced upregulation of p57 was effectively diminished (<1.3-fold; Fig 1C).…”
Section: P57 Expression Is Indirectly Upregulated By Tgfβ In Primitivsupporting
confidence: 92%
“…However, the molecular mechanism underlying TGFβ-induced proliferation arrest is largely unknown. Interestingly, TGFβ has been found to induce expression of the cell cycle inhibitor p57 in HSPCs 13,14 and this activation is crucial for TGFβ-induced cell cycle arrest in vitro 13 HSCs from Smad4 KO mice while p57 expression was significantly reduced. Still, deletion of Gata2 had strong impact on p57 baseline levels in hematopoietic progenitor cells as well as on TGFβ-induced upregulation of p57 and proliferation arrest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations